Healthcare Professionals' Beliefs, Attitudes, Knowledge, and Behavior Around Vaping in Pregnancy and Postpartum: A Qualitative Study. Issue 3 (5th July 2020) - Hunter, Abby; Yargawa, Judith; Notley, Caitlin; Ussher, Michael; Bobak, Alex; Murray, Rachael L; Nath, Srabani; Cooper, Sue
Abstract: Introduction: Finding effective ways to help pregnant women quit smoking and maintain long-term abstinence is a public health priority. Electronic cigarettes (ie, vaping) could be a suitable cessation tool in pregnancy for those who struggle to quit; however, healthcare professionals (HCP) must be informed about these devices to offer appropriate advice. This study used the Capability, Opportunity, Motivation, and Behavior (COM-B) model and Theoretical Domains Framework (TDF) to explore HCP attitudes towards vaping in pregnancy and postpartum; beliefs about the health risks of vaping; perceived barriers and facilitators of vaping in pregnancy; knowledge of current guidelines and policies; and training needs. Methods: Interviews ( n = 60) were conducted with midwives ( n = 17), health visitors ( n = 10), general practitioners ( n = 15) and stop smoking specialists ( n = 18) across the United Kingdom. Interview transcriptions were analyzed thematically using the framework approach and the COM-B. Results: Discussing vaping as a tool for quitting smoking in pregnancy was prevented by a lack of capability (limited knowledge of vaping, lack of training in smoking cessation); lack of opportunity (restricted by organizational policies and guidelines, lack of time and financial issues impacting on training), and negative social influences (sensationalist media and stigma associated with vaping in pregnancy); and lack of motivation (fear of future litigation and comebacks should adverse effects from vaping arise). Conclusions: Factors related to capability, opportunity, and motivation were identified that influence HCPs attitudes and behaviors towards vaping in pregnancy. Gaps in knowledge and training needs were identified, which could inform the development of targeted vaping training. Implications: Vaping could be suitable in pregnancy for those struggling to quit smoking. However, HCPs must be informed about these devices to offer appropriate advice. These data extend our knowledge of factors influencing HCP attitudes and behaviors towards vaping in pregnancy. Generally, vaping was perceived as safer than cigarettes, but a perceived lack of evidence, health and safety risks, dependency, and regulation issues were concerning. Considering our findings, greater efforts are needed to ensure HCPs are sufficiently informed about vaping and guidelines available. More importance should be placed on training for all HCPs who have contact with pregnant women.